İslam hukuku ve tıpta kadınlara özel haller - Bulut, Kevser (My University, 2020)
İslam hukuku ve tıp alanında kadınlara ait özel halleri ele alan bu çalışmada konu ile ilgili olarak mezheplerin içtihatları ve günümüzdeki tıp verileri mümkün olduğunca mukayese edilmiştir. Günden güne yenilik arz eden tıbbın, bu hususta geldiği noktada hangi görüşlerin daha fazla kabul göreceği konusunda gerekçeler bulunmaya çalışılmıştır. İslam hukukunda ise hakkında yalnızca bir âyet-i kerime ve birkaç hadis-i şerif olan bu konuda verilen fetvalar da genellikle tecrübe ve akıl yürütmeye dayalıdır. Dolayısıyla kadınların biyolojik yapılarına göre değişiklik arz eden bu konunun dini temelleri tespit edilmeye çalışılmıştır.

In this study, which deals with the special cases of women in the field of Islamic law and medicine, the jurisprudence of the sects and current medical data have been compared as much as possible. At the point where medicine, which is innovating day by day, comes to this point, it has been tried to find reasons for which views will be accepted more. In Islamic law, fatwas given on this subject, which is only a verse and a few hadiths, are generally based on experience and reasoning. Therefore, the religious basis of this subject, which is based on a very limited number of sources and varies according to the biological structures of women, was tried to be determined.
Keywords: fıkıh; fıqh; hayd; hayız; Islam; Islamic law; İslam; İslam hukuku; medicine; Mezhepler; Schools of Islamic law; tıp